Teacher communication in technology enhanced mathematics classrooms: effects on students conceptual understanding and mathematical creativity - Nuryadin, Aliman; Firdaus, Muhamad; Astuti, Reni (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study aims to investigate the influence of teacher communication skills on junior high school students’ mathematical conceptual understanding and creativity in classroom learning. Method: A quantitative explanatory research design was employed. The participants consisted of 34 junior high school students selected through purposive sampling. Data were collected using a teacher communication questionnaire, a mathematical conceptual understanding test, and a mathematical creativity test, supported by structured classroom observations to capture communication practices during instruction. All instruments were validated by experts and demonstrated acceptable reliability. Data analysis involved descriptive statistics and multiple linear regression, preceded by tests of normality, linearity, and multicollinearity to ensure the appropriateness of the regression model. Findings: The findings indicate that teacher communication has a significant effect on students’ mathematical conceptual understanding (t = 4.42, p < 0.001, R² = 0.364) and mathematical creativity (t = 3.54, p = 0.001, R² = 0.299). Students showed better conceptual comprehension when teachers provided clear, step-by-step explanations, used visual representations, and facilitated open dialogue. Mathematical creativity increased when students were encouraged to explore multiple solution strategies in a supportive communicative environment. Significance: This study highlights teacher communication as a key instructional factor influencing both conceptual understanding and creativity in mathematics learning. The findings suggest that strengthening teachers’ communication skills can enhance learning quality and support the development of meaningful and creative mathematical thinking in junior high school classrooms.